Analysis of Information Technology Services Using the ITIL V.4 Framework on the Ferizy E-Ticketing Application of PT. ASDP Indonesia Ferry, Merak Branch - Fyrsty Ashra Nisa; Yulhendri (Jurnal Teknologi Informatika dan Komputer, 2026)
The ITIL 4 framework is one of the most popular ITSM approaches, offering best practices for managing IT services. ITIL 4 introduces the concept of a Service Value System (SVS), providing comprehensive guidance for generating value through IT services. Digitalization in the maritime transportation sector has made significant progress, including through the implementation of an e-Ticketing system in ferry operations. PT ASDP Indonesia Ferry (Persero) Merak Branch has developed a digital system to facilitate ticket purchases and reduce physical queues at ports. ITIL 4 introduces the concept of a Service Value System (SVS), providing comprehensive guidance for generating value through Information Technology services. Evaluation using ITIL 4 is important for identifying imperfect service processes. Several practices such as Incident Management, Service Request Management, Problem Management, and Continual Improvement can be applied to identify service weaknesses that need to be addressed. By implementing ITIL 4, companies can improve IT management so that ticket purchasing processes, data validation, and payment transactions run smoothly and without interruption. Based on these four aspects, it can be concluded that the quality of information technology services in the Ferizy e-Ticketing application of PT ASDP Indonesia Ferry Merak Branch has been running well and is in line with the principles of ITIL 4, although there are still several aspects that can be developed further.